2015
DOI: 10.21831/jpv.v5i1.6074
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas model blended learning terhadap motivasi dan tingkat pemahaman mahasiswa mata kuliah algoritma dan pemrograman

Abstract: AbstrakPenelitian ini bertujuan untuk (1) (2) THE EFFECTS OF BLENDED LEARNING MODEL ON THE STUDENT'S MOTIVATION AND UNDERSTANDING ON THE SUBJECT OF ALGORITHMS AND PROGRAMMING Abstract This research aims (1) to determine the differences in motivation and understanding level of the students between learning model of blended learning and the conventional, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
34

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 6 publications
2
21
0
34
Order By: Relevance
“…This research stated that students who learn to use blended learning have higher learning outcomes than students who learn directly. Other research reported that effective blended learning can increase student motivation and understanding (Bibi & Jati, 2015), there is a significant influence on the use of blended learning models using Edmodo on student learning outcomes (Susilawati, 2018). These results can be concluded that blended learning can improve the quality of learning for finding information and knowledge based on real experience to produce products.…”
Section: Blended-learningmentioning
confidence: 99%
“…This research stated that students who learn to use blended learning have higher learning outcomes than students who learn directly. Other research reported that effective blended learning can increase student motivation and understanding (Bibi & Jati, 2015), there is a significant influence on the use of blended learning models using Edmodo on student learning outcomes (Susilawati, 2018). These results can be concluded that blended learning can improve the quality of learning for finding information and knowledge based on real experience to produce products.…”
Section: Blended-learningmentioning
confidence: 99%
“…Belajar mandiri adalah belajar yang aktif dan partisipatif untuk mengembangkan diri masing-masing individu yang tidak terikat dengan kehadiran, pertemuan tatap muka di kelas, dan kehadiran teman di sekolah, dan tidak mudah terpengaruh oleh pihak lain. Sejumlah penelitian yang menerapkan model pembelajaran blanded learning adalah (So & Brush, 2008;Sjukur, 2012;Syarif, 2012;Prayitno, 2015;Ningsih & Jayanti, 2016), yang telah menerapkan media kahoot adalah (Nugraha, 2018;Ningrum, 2018;Fitriani, Buchori & Nursyahidah, 2019), sementara itu yang menganalisis motivasi belajar siswa (Bibi & Jati, 2015;Hamdu, & Agustina, 2011) dan yang menganalisis kemandirian belajar siswa adalah (Suhendri, 2011;Rachmayani, 2014).…”
unclassified
“…Pemanfaatan multimedia dalam pembelajaran telah banyak dilaporkan mampu meningkatkan minat dan motivasi dan hasil belajar peserta didik dari mulai tingkat sekolah dasar hingga perguruan tinggi (Ali, 2009;Prawiro & Irawan, 2012). Hasil penelitian lain tentang implementasi e-learning dengan berbantuan multimedia dilaporkan secara signifikan dapat meningkatkan hasil belajar siswa (Kusumaningrum & Marpanaji, 2014) Menurut Heinze (2008) beberapa penelitian menunjukkan bahwa blended learning dapat meningkatkan hasil belajar sama dengan atau lebih tinggi dari mahasiswa yang belajar secara konvensional atau sepenuhnya online, meskipun tingkat keberhasilan bervariasi antara disiplin ilmu (Bibi & Jati, 2015).…”
Section: Abstract Blended Learning; Learning Outcomes; Student Percepunclassified
“…Hasil penelitian yang serupa dilaporkan oleh Bibi & Jati (2015), bahwa tingkat pemahaman mahasiswa Program Studi Pendidikan Teknologi Informasi dan Komputer STKIP PGRI Pontianak untuk mata kuliah Algoritma dan Pemrograman mengalami peningkatan secara signifikan melalui penerapan blended learning dibanding kelas konvensional. Hasil penelitian lain juga dilaporkan bahwa implementasi blended learning memberikan hasil belajar yang baik pada mahasiswa semester IV pada materi persamaan diferensial (Ningsih & Jayanti, 2016).…”
Section: Pembahasanunclassified